Laparoscopic-assisted peritoneal dialysis catheter insertion with two 5-mm ports: Complications and outcomes of 30 cases - Kung-Ning Hu; Kun-Hung Shen; Chih-Chiang Chien; Chien-Liang Liu (Formosan Journal of Surgery, 2017)
Introduction: End-stage renal disease has high prevalence in Taiwan, and peritoneal dialysis (PD) is one of the effective treatments. Although the open catheter placement method is more popular, the laparoscopic method is proven to be superior. We present our initial experience with laparoscopic PD catheter insertion. Materials and Methods: We set one 5-mm trocar over the periumbilicus with another assisting 5-mm trocar in a region about 3 cm lateral to the umbilicus. Abdominal exploration using laparoscopy is performed, and enterolysis is also performed if needed. The PD catheter is inserted through the assisted trocar deep into the Douglas pouch under vision. Finally, we check the final condition under laparoscopy and close the wound. Results: A total of thirty patients (median age 56.5 years old, 15 women) underwent this procedure. No intraoperative complications were noted, and the mean operation time was 32 min. Two postoperative complications were found (2/30, 6.7%). Delayed bleeding was noted due to abdominal wall vessel injury while setting the trocar. The vessel was sutured under laparoscopy, which stopped the bleeding. The other complication was tube dysfunction due to omentum wrapping. Laparoscopic revision of the tube was performed. All the complications could be resolved, and the PD was continued. The mid-term tube function at follow-up (at least 16 months) was acceptable in all cases. Conclusions: Laparoscopic-assisted PD catheter insertion is a feasible procedure that can reduce wound pain with acceptable PD function.